Shifts in the Source and Composition of Dissolved Organic Matter in Southwest Greenland Lakes Along a Regional Hydro‐climatic Gradient. Issue 12 (29th December 2017) - Osburn, Christopher L.; Anderson, Nicholas J.; Stedmon, Colin A.; Giles, Madeline E.; Whiteford, Erika J.; McGenity, Terry J.; Dumbrell, Alex J.; Underwood, Graham J. C.
Abstract: Dissolved organic matter (DOM) concentration and quality were examined from Arctic lakes located in three clusters across south‐west (SW) Greenland, covering the regional climatic gradient: cool, wet coastal zone; dry inland interior; and cool, dry ice‐marginal areas. We hypothesized that differences in mean annual precipitation between sites would result in a reduced hydrological connectivity between lakes and their catchments and that this concentrates degraded DOM. The DOM in the inland lake group was characterized by a lower aromaticity and molecular weight, a low soil‐like fluorescence, and carbon stable isotope (δ 13 C‐DOC) values enriched by 2‰ relative to the coastal group. DOC‐specific absorbance (SUVA254 ) and DOC‐specific soil‐like fluorescence (SUVFC1 ) revealed seasonal and climatic gradients across which DOM exhibited a dynamic we term "pulse‐process": Pulses of DOM exported from soils to lakes during snow and ice melt were followed by pulses of autochthonous DOM inputs (possibly from macrophytes), and their subsequent photochemical and microbial processing. These effects regulated the dynamics of DOM in the inland lakes and suggested that if circumpolar lakes currently situated in cool wetter climatic regimes with strong hydrological connectivity have reduced connectivity under a drier future climate, they may evolve toward an end‐point of large stocks of highly degraded DOC, equivalent to the inland lakes in the present study. The regional climatic gradient across SW Greenland and its influence on DOM properties in these lakes provide a model of possible future changes to lake C cycling in high‐latitude systems where climatic changes are most pronounced. Plain Language Summary: Arctic regions are currently experiencing change due to warming climate, and Arctic lakes are natural recorders of this change. We conducted a study of 20 Arctic lakes situated across a climatic gradient in southwest Greenland ranging from cool and wet coastal region to a warm and dry inland region. We found that Arctic carbon cycles are responding to this change by concentrating dissolved organic carbon (DOC), a collection of molecules that form the basis of lake food webs, which may be very old and represent long‐term accumulation of carbon in these lake waters. We suspect that the force driving this change is a loss of the connectivity between these lakes and their watersheds. Under this scenario, lakes receive less organic carbon from soils in their surrounding watersheds and perhaps more from fringing aquatic plants. Moreover, earlier loss of lake ice may lead to longer open water periods and the chance for sunlight to convert DOC to carbon dioxide, representing a feedback to regional climate. As global change influences the Arctic broadly, modifications to the hydrologic connectivity of lakes to their watersheds may have important implications for Arctic inland C cycling. Key Points: Mean annual precipitation exerted a strong control on quantity and quality of lake DOM DOM in lakes with low hydrological connectivity experienced substantial microbial and photochemical degradation The climatic gradient under which the SW Greenland lakes currently exist may reflect the future changes in Arctic lake C cycling to be expected